Fundamentals of labor economics - Hyclak, Thomas; Johnes, Geraint; Thornton, Robert J. (South-Western/Cengage Learning, 2013)
Labor Economics, 2e, International Edition covers the essential aspects of modern labor economics from an international perspective, providing students with a comprehensive survey of economic theory and empirical evidence on purely competitive labor markets. In addition, the authors examine the impact of imperfect competition, incomplete information and uncertainty, and institutional factors-stemming from laws, unions, and human resource policies-on wages and employment opportunities.